Riddah (Apostasy) in Islamic Jurisprudence: The Views of The Jurists - Abdullahi, Ja’afar Agaji (South Asian Journal of Social Sciences and Humanities, 2021)
Islam is a religion that recognizes the freedom of thought and faith. That is why there is no single incidence where force is used so as to convert others throughout the history. Thus, any person feels and willingly accepts it, is not allowed to go out, i.e. to commit ‘riddah’ (apostasy). This paper is an attempt to highlight on ‘riddah’, its conditions before it is established; mode of its evidence(s); its punishment and the mode of execution; based on the nusus as well as the opinions of the Fuqaha (jurists). Thereupon, the paper postulates that the basic aim and objective behind the punishment of apostasy is the preservation of Islamic faith, because the whole bedrock of the religion (Islam) and its laws rests on faith. So, by committing the crime (of apostasy) many issues are involved: the issue of withdrawal from the dominion of the Almighty God, there is blasphemy; heresy; and mockery to Islamic community. Considering all these, the crime (of apostasy) is made punishable in order to close all avenues that will humiliate the blessed nation of Islam.